Peroral endoscopic myotomy for complex achalasia and the POEM difficulty score: An update - Carmen Ching Hui Yee; Michael Youssef; Matthew Woo; Robert Bechara (DEN Open)
Abstract Objectives We present an update on the (peroral endoscopic myotomy (POEM) difficulty score [PDS] by introducing a novel knife with waterjet functionality. Methods This is a retrospective review of patients who underwent POEM between May 2018 and July 2023 at the Kingston Health Sciences Center. Demographic and procedural variables were compared using descriptive and inferential statistics. Results One hundred thirty‐nine consecutive POEMs were included in the study. Seventy‐four (56.7% male; aged 56.7 ± 16.5 years) complex achalasia (CA) and 65 (55.4% female; aged 47.3 ± 20.2 years) non‐CA POEM procedures were performed. PDS correlates moderately with procedural efficiency with a correlation coefficient of 0.595 (Spearman's p < 0.001). The mean efficiency for non‐CA was 3.3 ± 1.2 min/cm compared to CA as follows: type III 3.3 ± 1.3 min/cm; prior myotomy 5.3 ± 2.3 min/cm; ≧4 prior procedures 4.0 ± 1.7 min/cm; sigmoid type 5.2 ± 2.4 min/cm. The median PDS for non‐CA was 1 (1–5). In comparison, the median PDS for CA is as follows: type III 3 (2–4); prior myotomy 4 (3–5); ≧4 prior procedures 3 (1.25–4); sigmoid type 3 (2–4). PDS excluding the presence of spastic contractions correlated better with procedural velocity, with a correlation coefficient of 0.645 (Spearman's p < 0.001). Conclusions PDS continues to moderately correlate with procedural efficiency using the novel knife. The presence of spastic contractions correlated poorly with procedural efficiency. Thus, it may be omitted in further studies.